2011
DOI: 10.2528/pier10120603
|View full text |Cite
|
Sign up to set email alerts
|

DIAGONAL HORN GAUSSIAN EFFICIENCY ENHANCEMENT BY DIELECTRIC LOADING FOR SUBMILLIMETER WAVE APPLICATION AT 150 GHz

Abstract: Abstract-The dielectric pyramid loaded and the dielectric cone loaded diagonal horn working at 150 GHz are investigated by using Gaussian beam mode analysis. With extremely low cross-polarized and axially symmetrical field distribution in the horn aperture, the calculated fundamental Gaussian mode coupling achieves about 98%. The far field radiation patterns of the two antennas are analyzed using fundamental Gaussian mode aperture-field distribution model whose results agree with high-accuracy CST TM software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Thus, the requirements of the communication systems and terminals are very severe, as it can be easily seen in the literature [5][6][7][8][9]. The severe requirements usually imply the use of higher and higher working frequencies, such as microwave or even millimeter band [10,11]. One important issue related to the radiating terminals is its proper and accurate characterization [12] and one usual problem is the accurate determination of the radiation pattern and the phase center of the antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the requirements of the communication systems and terminals are very severe, as it can be easily seen in the literature [5][6][7][8][9]. The severe requirements usually imply the use of higher and higher working frequencies, such as microwave or even millimeter band [10,11]. One important issue related to the radiating terminals is its proper and accurate characterization [12] and one usual problem is the accurate determination of the radiation pattern and the phase center of the antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Within this range, a considerable research effort is currently concentrated on technological developments aiming to improve characteristics and performance of devices for emitter and receiver systems. A very important number of comprehensive reviews [1,2] on the state-of-the-art of THz technology [3][4][5] can be found in the literature . A non-exhaustive list of applications includes astronomy [6], security scanning [7], explosives detection [8], medical imaging and biology [9,10] and atmospheric remote sensing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the confinement of power in a region of air by non-conducting materials may decrease noticeably the attenuation of the waveguide. The resulting structure may be specially useful in highly sensitive applications [13], in the design of horn antennas with an enhanced efficiency [14] or in near-field probing systems [15].…”
Section: Introductionmentioning
confidence: 99%